Disseminated Nocardiosis in renal transplant recipient under therapy for pulmonary tuberculosis: a case report. (December 2017) - Khadka, Priyatam; Basnet, Ramesh; Khadka, Pratap; Shah, Dibya; Pokhrel, Bharat; Rijal, Basista; Sherchand, Jeevan
Abstract Background Nocardiosis is an opportunistic infection in a patient with underlying immune suppression and organ transplant. Clinical syndromes are varied and ranges from pulmonary, disseminated, cutaneous along with central nervous system involvement. Case presentation Herein, we report a rare case of disseminated pulmonary nocardiosis with cerebral manifestation in a 66 year-old-Nepali farmer; with a history of renal transplantation and undergoing therapy for pulmonary tuberculosis. Radiographic imaging revealed multiple opacities of varying sizes in bilateral lung field mediastinal, retroperitoneal lymphadenopathy, and ill-defined lesion with surrounding edema seen in left occipitoparietal region of brain. Bacteriological assessments of bronchoalveolar lavage and purulent fluid extracted intra-operatively from the lesion confirmed the case as Nocardiosis. Conclusion Disseminated Pulmonary nocardiosis with central nervous system involvement carries a poor prognosis. However, early diagnosis of the case, the administration of appropriate antibiotic, stereotactic aspiration alone or craniotomy has a successful outcomes even in a post renal transplant patient treated with anti tuberculosis treatment.